2009
DOI: 10.1007/dcr.0b013e3181a0a37e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Prediction of an Involved Surgical Resection Margin in Low Rectal Cancer

Abstract: Significant magnetic resonance imaging positive resection margin predictors are tumor into or beyond the intersphincteric plane and magnetic resonance imaging tumor regression grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…In detail, patients with suspected tumor tissue (primary tumor or affected lymph node) over 1 mm away from the circumferential resection margin (CRM) and MRI-predicted T1/T2/T3a/T3b regardless of lymph node status are considered as Bgood prognosisâ nd can safely be treated by primary surgery with adjuvant chemotherapy depending on lymph node status [16]. In addition, lower rectal tumors <5 cm from the anal verge are also categorized as good if not encroaching into the intersphincteric plane or levator muscles [17]. Even in the MERCURY concept, MRIpositive lymph nodes remain an important issue.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, patients with suspected tumor tissue (primary tumor or affected lymph node) over 1 mm away from the circumferential resection margin (CRM) and MRI-predicted T1/T2/T3a/T3b regardless of lymph node status are considered as Bgood prognosisâ nd can safely be treated by primary surgery with adjuvant chemotherapy depending on lymph node status [16]. In addition, lower rectal tumors <5 cm from the anal verge are also categorized as good if not encroaching into the intersphincteric plane or levator muscles [17]. Even in the MERCURY concept, MRIpositive lymph nodes remain an important issue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Salerno et al . reported that MRI can predict invasion to the ISS 62. The utility of MRI has been emphasized for facilitating a successful operation with negative CRM 63, 64.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one limitation of our study. Recently, in order to enhance the accuracy of MRI in staging low rectal cancer, some studies proposed a novel MRI staging technique, which was based on the relationship of the tumor to the levators and individual components of the sphincter complex [53,54,55]. However, the benefit of the new staging technique is not clear and larger prospective studies are needed to confirm its benefit.…”
Section: Discussionmentioning
confidence: 99%